2015
DOI: 10.1111/bjh.13461
|View full text |Cite|
|
Sign up to set email alerts
|

Laboratory parameters identify familial haemophagocytic lymphohistiocytosis from other forms of paediatric haemophagocytosis

Abstract: SummaryHaemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome of immune dysregulation and is classified as primary or secondary according to the underlying aetiology. The treatment strategies recommended for these two groups differ substantially; however, it is thought to be impossible to predict the underlying causes of HLH using conventional laboratory tests. Recent studies show that serum levels of soluble interleukin-2 receptor (sIL2R) and ferritin are useful for differentiating some form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In addition, the HScore designed by Fardet [23] appeared to be more sensitive in early diagnosis of adult HLH. Other laboratory parameters, such as TNF-α, IFN-γ, IL-6 and presepsin, are helpful in distinguishing M-HLH from others [24,25]. In our study, a ferritin level of over 10000 ng/mL was found in 20 of 26 patients, while sCD25/ferritin ratio>2 was found in 5 of 7 patients.…”
Section: Discussionsupporting
confidence: 44%
“…In addition, the HScore designed by Fardet [23] appeared to be more sensitive in early diagnosis of adult HLH. Other laboratory parameters, such as TNF-α, IFN-γ, IL-6 and presepsin, are helpful in distinguishing M-HLH from others [24,25]. In our study, a ferritin level of over 10000 ng/mL was found in 20 of 26 patients, while sCD25/ferritin ratio>2 was found in 5 of 7 patients.…”
Section: Discussionsupporting
confidence: 44%
“…Our observations with respect to the HLH mouse model in the absence of IFN-g are of clinical relevance because, recently, a first report appeared on two IFN-gR-deficient patients who acquired HLH after herpesvirus and mycobacterial infection (63). In these patients, the syndrome must have developed in an IFN-g-independent way, arguing against the existence of a general pathogenic pathway that would cause both primary and secondary HLH (19,64). Alternative pathways, also IFN-g-independent ones (13,18,65), are capable of inducing a similar syndrome.…”
Section: Discussionmentioning
confidence: 80%
“…In this cohort, all primary HLH cases belong to type2 HLH including FHL2 and XLP1, and it is not surprising that we can not find difference of degranulation between primary HLH and secondary HLH groups. Yasumi et al proposed that the percentage of total lymphocytes, serum levels of LDH, and the sIL2R/ferritin ratio could differentiate familial from secondary HLH [ 32 ]. In this study, when we compare to the secondary HLH patients, primary HLH patients have higher percentage of lymphocytes (mean level 75.3 % vs 48.0 %, P = 0.012), and lower percentage of neutrophils (12.8 % vs 40.7 %, P = 0.012), which is consistent with Yasumi et al’s findings.…”
Section: Discussionmentioning
confidence: 99%